Strategies for High‐Performance Solid‐State Triplet–Triplet‐Annihilation‐Based Photon Upconversion - Lin, Ting‐An; Perkinson, Collin F.; Baldo, Marc A. (Advanced materials (Weinheim), 2020)
Photon upconversion via triplet–triplet annihilation (TTA) has achieved high efficiencies in solution and within polymer matrices that support molecular migration systems. It has diverse potential applications including bioimaging, optical sensors, and photovoltaics. To date, however, the reported performance of TTA in rigid solid‐state systems is substantially inferior, which may complicate the integration of TTA in other solid‐state devices. Here, solid‐state loss mechanisms in a green‐to‐blue upconversion system are investigated, and three specific losses are identified: energy back transfer, sensitizer aggregation, and triplet–charge annihilation. Strategies are demonstrated to mitigate energy back transfer and sensitizer aggregation, and a completely dry‐processed solid‐state TTA upconversion system having an upconversion efficiency of ≈2.5% (by the convention of maximum efficiency being 100%) at a relatively low excitation intensity of 238 mW cm−2 is reported. This device is the first demonstration of dry‐processed solid‐state TTA comparable to solution‐processed solid‐state systems. The strategies reported here can be generalized to other upconversion systems and offer a route to achieving higher‐performance solid‐state TTA upconversion devices that are compatible with applications sensitive to solvent damage. Solid‐state triplet–triplet‐annihilation‐based photon‐upconversion systems are subject to losses from back transfer, molecular aggregation, and triplet–charge annihilation. Following strategies provided to mitigate these losses, a dry‐processed solid‐state device having comparable upconversion efficiency and threshold intensity to solution‐processed solid‐state systems is developed, offering a route for high‐performance upconversion devices compatible with applications sensitive to solvent damage.